2020
DOI: 10.2174/1381612826666200523174753
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Progress and Prospects of Dengue Drug Discovery Targeting NS5 RNA- Dependent RNA Polymerase

Abstract: : Dengue virus (DENV) infection threatens the health and wellbeing of almost 100 million people in the world. Vectored by mosquitoes, DENV may cause severe disease in human hosts called Dengue hemorrhagic fever (DHF)/Dengue shock syndrome (DSS), which are not preventable by any known drug. In the absence of a universally-accepted vaccine, a drug capable of inhibiting DENV multiplication is an urgent and unmet clinical need. Here we summarize inhibitory strategies by targeting either host biochemical pathways o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 114 publications
1
9
0
Order By: Relevance
“…So, we believe that if NNIs are designed for this site based on the aforementioned residues this may result in a similar mechanism of inhibition by causing displacement of the Δ1 loop, which will disrupt the functionality of the RdRp. T2 site : As per the T2 site of HCV RdRp ( Mittal et al, 2020 ) and allosteric site 1 of DENV RdRp ( Maddipati et al, 2020 ) below the thumb domain and C-terminal, we did not find any relevant or conserved residues in CoV-2 RdRp. P1 site: As per the P1 site of HCV RdRp (present adjacent to the active site on palm subdomain) ( Mittal et al, 2020 ), we found residues T687, N691, S759, D760, D761, and C813 of CoV-2 RdRp as structurally well-conserved residues with their corresponding residues T287, N291, G317, D318, D319, and C366 in HCV RdRp ( Figure 9B ).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…So, we believe that if NNIs are designed for this site based on the aforementioned residues this may result in a similar mechanism of inhibition by causing displacement of the Δ1 loop, which will disrupt the functionality of the RdRp. T2 site : As per the T2 site of HCV RdRp ( Mittal et al, 2020 ) and allosteric site 1 of DENV RdRp ( Maddipati et al, 2020 ) below the thumb domain and C-terminal, we did not find any relevant or conserved residues in CoV-2 RdRp. P1 site: As per the P1 site of HCV RdRp (present adjacent to the active site on palm subdomain) ( Mittal et al, 2020 ), we found residues T687, N691, S759, D760, D761, and C813 of CoV-2 RdRp as structurally well-conserved residues with their corresponding residues T287, N291, G317, D318, D319, and C366 in HCV RdRp ( Figure 9B ).…”
Section: Resultsmentioning
confidence: 71%
“…T2 site : As per the T2 site of HCV RdRp ( Mittal et al, 2020 ) and allosteric site 1 of DENV RdRp ( Maddipati et al, 2020 ) below the thumb domain and C-terminal, we did not find any relevant or conserved residues in CoV-2 RdRp.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations